Child Sacrifice in Rūparāma's Dharmamaṅgala. (13th June 2018) - Manring, Rebecca J
Abstract: The theme of sacrifice recurs in religious literature of many traditions, times, and places, and notions of parental sacrifice are even more common. But tales of human sacrifice are almost unheard of. Among the sacrifices parents make, the sacrifice of a child is the most unlikely; why would a deity demand such an offering, and what does that demand tell us about the deity's followers? Through skillful use of social inversions, bībhatsa rasa, and sacrifice, Rūparāma Cakravartī weaves a masterful tale early in his epic the Dharmamaṅgala which sets the tone for the rest of the epic and prepares his readers for the wonders to follow.